2017
DOI: 10.1158/1078-0432.ccr-16-1604
|View full text |Cite
|
Sign up to set email alerts
|

ADNP Is a Therapeutically Inducible Repressor of WNT Signaling in Colorectal Cancer

Abstract: Constitutively active WNT signaling is a hallmark of colorectal cancers and a driver of malignant tumor progression. Therapeutic targeting of WNT signaling is difficult due to high pathway complexity and its role in tissue homeostasis. Here, we identify the transcription factor ADNP as a pharmacologically inducible repressor of WNT signaling in colon cancer. We used transcriptomic, proteomic, and analyses to identify ADNP expression in colorectal cancer and cell biology approaches to determine its function. We… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 34 publications
1
24
0
Order By: Relevance
“…6,8,37 Different from mutations in other cancer types, mutations in the key regulatory factors of Wnt/b-catenin signaling are frequent events in colon cancer. 38 Constitutive activation of Wnt/b-catenin signaling, which was reflected by the translocation of b-catenin into the nucleus, may cause the reduction of E-cadherin and subsequent induction of EMT. 39 Until now, LncRNAs participating in the Wnt/b-catenin signaling-induced EMT are still seldom reported.…”
Section: Discussionmentioning
confidence: 99%
“…6,8,37 Different from mutations in other cancer types, mutations in the key regulatory factors of Wnt/b-catenin signaling are frequent events in colon cancer. 38 Constitutive activation of Wnt/b-catenin signaling, which was reflected by the translocation of b-catenin into the nucleus, may cause the reduction of E-cadherin and subsequent induction of EMT. 39 Until now, LncRNAs participating in the Wnt/b-catenin signaling-induced EMT are still seldom reported.…”
Section: Discussionmentioning
confidence: 99%
“…In previous studies, ADNP was associated with the de novo mutation that leads to autism-like spectrum disorder (18). However, a recent study suggested that negative ADNP expression in the colon activates the WNT signaling pathway, promoting colon cancer cell migration, invasion, and proliferation (15). We found that ADNP expression was significantly correlated with high pathological grade and advanced clinical stage, indicating that ADNP may be an oncogene of BC that can lead to tumor cell proliferation and tumorigenesis.…”
Section: Discussionmentioning
confidence: 59%
“…According to the previous research, ADNP loss-of-function mutations have been found to be related to carcinogenesis ( 14 ). It was reported that ADNP can suppress cellular migration, invasion, and proliferation via the WNT signaling pathway in colon carcinoma ( 15 ) and triple-negative breast cancer ( 16 ). By contrast, the activation of the ADNP signaling system, mediated by an endogenous pituitary adenylate cyclase-activating polypeptide, can increase the resistance of malignant peripheral nerve sheath tumor to H 2 O 2 -induced death with serum starvation ( 17 ).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Blaj et al showed that low-dose ketamine induced activity-dependent neuroprotector homeobox (ADNP) expression in a colorectal cancer model. ADNP in turn acted as a Wnt repressor which ultimately led to tumor growth inhibition and prolonged survival of tumor bearing animals [ 60 ].…”
Section: Csc-specific Treatment Approaches: Preclinical Settingmentioning
confidence: 99%